Ex Libris E. Skolepp / E. Okas. - Okass, Evalds (1915-2011) ([wydawca nieznany], 1961)
Akt kobiecy. Napis u góry: Ex Libris, wzdłuż lewej krawędzi: E. Skolepp. Sygnatura artysty i data w obrębie kompozycji.